Kinerja Model Fisik Konverter Energi Ombak Rangkaian Gear Searah pada Periode Ombak yang Bervariasi - Muchtar, Masjono; Manjang, Salama; Suriamiharja, Dadang A; Thaha, M Arsyad (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
To date there were few research on the effect of non-linearity properties of the ocean waves on the performance of wave energy converter (WEC), which uses a series of unidirectional gear. One such parameter is the variation of wave period. The influence of wave period variations on the performance of physical model of the wave energy converters have been investigated at the Hydraulics Laboratory, Department of Civil Engineering, Hasanuddin University Indonesia. This WEC physical model was fabricated and assembled at Politeknik ATI Makassar Indonesia. The investigation steps consists of physical model development, physical model investigation at wave flume prior to the wave period  variation, measuring input output parameters of the physical model under test and empirical model formulation based on observed data analysis. Physical model test carried out on the wave flume at the Hydraulics Laboratory of the Department of Civil Hasanuddin University, at a water depth of 25 cm, wave height between 5-9 cm and wave period between 1.2 - 2.2 seconds. Investigation result based on flywheel radial speed (RPM) and torque (Nm) indicated that calculated harvested power was inversely proportional with the wave period. The longer the period of the waves, the energy produced is getting smaller. The derived empirical formula was y = -85.598x + 208.53 and R² = 0.8881. Y is energy produced (Watt) and X is the wave period (Second). Formulations generated from this study could be used as a reference for future research in dealing with wave period variations on a design one way gear wave energy converter as a source of renewable energy.